Female Students' Mathematical Argumentation Ability Based on Self-Efficacy Level - Jagadianti, Gurit Wulan; Wijayanti, Pradnyo (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to investigate the mathematical argumentation abilities of female students based on their levels of self-efficacy. Mathematical argumentation is crucial in math education for mastering concepts and developing higher-order thinking skills. Self-efficacy relates to an individual's confidence in completing math tasks, including argumentation The research employs a quantitative approach, collecting data from 36 students in the Mathematics Education Program. Data was gathered through a self-efficacy questionnaire and math tasks related to statistics that assess students' mathematical argumentation. The findings indicate that mathematical argumentation abilities vary across different levels of self-efficacy. . Students with high self-efficacy do not always have strong mathematical arguments, and vice versa. The level of self-efficacy in students does not determine the strength of the mathematical arguments presented by students.